2022
DOI: 10.1097/md.0000000000030485
|View full text |Cite
|
Sign up to set email alerts
|

Impaired brain networks functional connectivity after acute mild hypoxia

Abstract: This study aimed to analyze the changes in brain networks functional connectivity of pilots exposed to simulated hypoxia using resting-state functional magnetic resonance imaging (fMRI). A total of 35 healthy male pilots exposed to 14.5% oxygen concentration (corresponding to an altitude of 3000 m) underwent resting-state fMRI scans. The independent component analysis (ICA) approach was used to analyze changes in the resting-state brain networks functional connectivity of pilots after hypoxic exposure, and 9 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
1
1
0
Order By: Relevance
“…This difference suggested that the hypoxic environment may alter the patterns of interaction among large-scale brain networks compared to normal ventilation status, resulting in broad changes in the neuro function. This founding was consistent with the results of RS-fMRI in previous studies on acute hypoxia and obstructive sleep apnea hypopnea syndrome (6,7). Similar effect was also reported in a recent study, Haller et al found that wearing masks may change the patterns functional connectivity with the salience network (18).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This difference suggested that the hypoxic environment may alter the patterns of interaction among large-scale brain networks compared to normal ventilation status, resulting in broad changes in the neuro function. This founding was consistent with the results of RS-fMRI in previous studies on acute hypoxia and obstructive sleep apnea hypopnea syndrome (6,7). Similar effect was also reported in a recent study, Haller et al found that wearing masks may change the patterns functional connectivity with the salience network (18).…”
Section: Discussionsupporting
confidence: 91%
“…This phenomenon was also confirmed by a large number of subsequent studies (4,5). Acute hypoxia and obstructive sleep apnea hypopnea syndrome lead to changes in spontaneous neural activity of the brain in the resting state (6,7). Previous studies have shown that changes in the composition of inhaled air flow and the increase of CO 2 concentration elevated the blood flow in cerebral arteries and affected the blood supply of the cortex (8).…”
Section: Introductionmentioning
confidence: 68%